Pitching & closing : everything you need to know about business development, partnerships, and making deals that matter - Taub, Alexander (McGraw-Hill Education, 2014)
"Alex Taub and Ellen DaSilva have written the bible for business development in startup land--a well-researched, easily accessible accounting of best practices and tips of the trade from the people who are leaders in opening and closing deals that define some of the most exciting new companies on the landscape.""I never thought I'd read a book that not only explains how nuanced business development can be, but also actually gives you what you need to take teams big and small to grow their business through partnerships. Impressive and fun to read."--Paul Murphy, CEO of Dots and Partner at Betaworks